Energy integration across electricity, heating & cooling and the transport sector - Sector coupling - Martin Wietschel; Anne Held; Benjamin Pfluger; Mario Ragwitz (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
[Summary and conclusions] A stronger integration across energy sectors can contribute to achieving climate targets, provided that fossil fuels are substituted by renewable energy sources. One analysis for the German energy market estimates the potential GHG-emission savings due to sector coupling to 50 Mio t of CO2 emissions by 2030 (see Wietschel et al. 2017). A high potential to reduce GHG-emissions in the short and medium term is provided by direct electrification options: e-mobility, heat pumps and electric blast furnace. In the longer term, trolley trucks may also contribute to GHG-emission reductions, but the technology is not yet mature and it will depend on the achievable technology and cost development. There are also options in the industry sector, including methanol, ammonium or refineries, but these options are still far from being economically efficient. Producing electricity mainly based on RES is crucial for exploiting the GHGemission reduction potential of sector coupling technologies. However, we believe that a timely market entry of sector coupling technologies is required in order to exploit potentials on a longer term. The current electricity mix still shows considerable shares of fossil fuels, but a further increase of the RES-E share is a precondition for exploiting the GHG-emission reduction potential of sector coupling technologies. Wietschel et al. (2017) suggest using options with high efficiencies and a high GHG-emission reduction potential in the early phase of the transformation mainly for reasons of public and social acceptance. Sector coupling technologies may also contribute to increasing energy efficiency (e.g. e-mobility, electric steel) and thus reduce GHG-emissions due to efficiency improvements. For example, heat pumps make use of the ambient heat and can therefore improve efficiencies. Wietschel et al. (2017) have estimated for Germany that final energy consumption can be reduced by 180 TWh due to the efficiency effect by 2030, whilst electricity demand of new applications would increase by 50 TWh. Finally, sector-coupling technologies can increase the flexibility of the power system, which can be particularly relevant for systems with high shares of variable RES-E. However, the flexibility potential of different options and technologies strongly differs. According to Wietschel et al. (2017) there are high potentials for e-mobility and electrode boilers in heating networks.
urn:nbn:de:0011-n-5971244
Keywords: 330